Pertanggungjawaban Pidana Pelaku yang Memiliki Riwayat Gangguan Jiwa pada Perkara Pembunuhan di Kabupaten Kebumen - Rendradi Suprihandoko (Syntax Idea)
The problem faced is What is the criminal responsibility of the perpetrators of the crime of murder if the perpetrator has a history of psychiatric disorders in decision number 174/Pid.B/2018/PN.Kbm, and what factors are the cause of the murder case committed by the perpetrator who has a history of psychiatric disorders in decision number 174/Pid.B/2018/PN.Kbm, as well as how the judge's legal considerations in imposing a crime on the perpetrator murder criminal who has a history of mental disorders in decision number 174/Pid.B/2018/PN.Kbm? offender with a history of mental disorders. This type of research is normative legal research with the approach method used is normative juridical (normative legal research method). The research findings based on psychiatric examination and observation by specialist doctors at RSJ Prof. Dr. Soerojo Magelang on the suspect Sumudi bin Sodali include laboratory results within normal limits and for psychological examinations, intelligence level (IQ) is 75-79 /borderline and anti-social personality disorder with paranoia. As for other diagnoses, namely: Axis I (aspect I): F60.2 Anti-social personality disorder, meaning that the patient has a behavioral disorder characterized by not caring about social norms, cheating or lying, often committing criminal acts, and no sense of guilt and regret.; Axis II (aspect II): Paranoid personality trait meaning that the patient is easily suspicious.; Axis III (aspect III): No diagnosis, meaning no physical illness is found; Axis IV (aspect IV): Problems related to law /criminal means that the patient often violates the law/criminal.; Axis V (aspect V): Global function assessment 70-61, meaning some difficulties in social and work functioning, but in general functioning well, having a significant relationship. The conclusion is that based on the expert's statement that for cases of law violations that have been committed by a patient named Mr. SUMUDI bin SODALI towards his own biological mother is part of a mental disorder, but not a severe mental disorder (psychotic) so that the patient can still direct his will consciously.